Simulation Research on Grid-side Voltage Fluctuation of DC Source with 12-pulse Rectifier - YING Ting; XU Wei; ZHANG Yu; LIANG Zhiwei (Kongzhi Yu Xinxi Jishu)
Taking 12-pulse DC source as a study object, it described the mechanism of voltage fluctuation, analyzed and calculated the influences. The methods of suppressing fluctuation were proposed. Matlab/Simulink software was used to establish models for 12-pulse DC source, and the effectiveness of the methods was validated by simulation.